The Adsorption Capacity and Geotechnical Properties of Modified Clay Containing SSA Used as Landfill Liner-Soil Materials - Haijun Lu; Yiqie Dong; Jixiang Li; Changhong Wang (Journal of Chemistry)
The potential of clay containing 0~5% sewage sludge ash (SSA) is assessed for use as a landfill liner-soil material. Low temperature N2 adsorption, batch adsorption, permeability, and unconfined compressive strength tests are performed to evaluate pore structure, adsorption capacity, hydraulic conductivity, and unconfined compressive strength of the clays. The pore size distribution of the modified clay containing SSA is mainly composed of micropores (<2 nm) and mesopores (2~7 nm). With the increasing of SSA from 0% to 5%, the adsorption capacity of Zn(II) and Cu(II) to the clay increases 37% and 273%, respectively. The hydraulic conductivity of modified clay is from 3.62 × 10−8 to 2.17 × 10−8 cm/s. At SSA = 3%, the unconfined compressive strength of the clay reaches the maximum value of 601.1 kPa. After the clay containing SSA is contaminated by acid and alkali chemical solutions, the amount of mesopores and hydraulic conductivity increase. The adsorption capacity and unconfined compressive strength of contaminated clay decrease about 2∼44% and 25.7∼38.2%, respectively. The modified clay containing SSA can meet the adsorption and geotechnical requirement of landfill liners.